Modelling of a two-dimensional photonic crystal as an antireflection coating for optoelectronic applications - Przybylski, D.; Patela, S. (Opto-Electronics Review, 2019)
In article a two-dimensional photonic crystal (PhC) is considered and modelled as a new generation antireflection coating for optoelectronic devices. Traditional antireflective coatings (ARCs) reduce the reflection of the radiation only – the new generation of antireflective coatings should affect the distribution of the radiation also. Such functionality can be provided by the two-dimensional PhC which reduce the reflection and scatter transmitted light. Prior to the fabrication, the PhCs should be designed and analysed. Results of the analysis should provide quantitative means for choice of materials and design solutions. In work, we analyse the electromagnetic field distribution as Poynting vectors inside the materials of optoelectronic devices, in order to investigate the possibility of improving the construction of future optoelectronic devices. Furthermore, we calculate the reflection and transmission of that ARC. It’s a complex optic analysis of new generation of ARC. The numerical analysis has been performed with the FDTD method in Lumerical Software. In work, we consider the two-dimensional photonic crystal on the top surface of optoelectronic structures. We compared the results with the traditional ARC from these same parameters as PhC: thickness and material. As an example, we presented the application of modelled, photonic crystal, thin-film, GaAs solar cells with PhC on top. The efficiency of this solar cell, using the photonic crystal, was improved by 6.3% over the efficiency of this same solar cell without PhC. Thus, our research strongly suggests that the unique properties of the photonic crystal could be used as a new generation of ARC.